TARGET OPERATION (TO) GAME: TARGETING AT ATTRIBUTION THEORY IN TEACHING SPEAKING - Weganofa, Riza (Jurnal Ilmiah Bahasa dan Sastra, 2014)
ABSTRACT Attribution theory derives from psychology in language teaching. This theory believes that success or failure in language teaching might be upon four main sets of attribution: ability, effort, luck, and task difficulty. Some L2 learners, specifically non-English department students find difficulty in speaking due to either they view themselves as incapable in learning English, they do not push themselves hard enough to learn English, or they perceive that the task given is too difficult to be completed. Target Operation (TO) Game is proposed to accommodate the problems that later, determines the success or failure of learning speaking. This research provides some examples of tasks of TO Game, descriptive results of the four sets of attribution, and the outcome of the implementation of the game.Â Keywords: attribution theory, Target Operation (TO) Game, speaking